Laparoscopic hepatectomy for liver metastasis of lung large-cell neuroendocrine carcinoma: A case report. (2019) - Yamane, Hisoka; Yoshida, Sachiko; Yoshida, Toshihiko; Nishi, Masayasu; Yamagishi, Takashi; Goto, Hironobu; Otsubo, Dai; Furutani, Akinobu; Matsumoto, Taku; Fujino, Yasuhiro; Kajimoto, Kazuyoshi; Sakuma, Toshiko; et al.
Highlights: Lung large-cell neuroendocrine carcinoma (LCNEC) is an aggressive and a rare type of lung cancer. The prognosis of LCNEC with distant metastasis is extremely poor. Surgical resection for liver metastasis of LCNEC may improve prognosis. Abstract: Introduction: Lung large-cell neuroendocrine carcinoma (LCNEC) is an aggressive and a rare type of lung cancer, and the prognosis of LCNEC with distant metastasis is extremely poor, with a five-year survival rate of 0%. Here, we report a case of laparoscopic hepatectomy for liver metastasis of lung LCNEC. Presentation of case: A 63-year-old man received a routine physical examination, and abnormal chest radiographic findings were observed; chest computed tomography (CT) in our hospital revealed that the patient had left pneumothorax and a lesion measuring 18 mm in the inferior lingular segment of the lung. The patient underwent thoracoscopic lobectomy, and the final pathological diagnosis was lung LCNEC. Four years after surgery, abdominal CT revealed a mass measuring 27 mm in the liver. The patient underwent laparoscopic partial hepatectomy, and postoperative pathological examination showed liver metastasis of LCNEC. There was no sign of recurrence 6 months after hepatectomy. Discussion: LCNEC with distant metastasis has a poor response to systemic chemotherapy, and the median survival time of patients with distant metastasis is estimated to be approximately 6 months, with a five-year survival rate of 0%. Although the common site of metastasis from LCNEC is the liver, there are no previous reports of hepatectomy for liver metastasis of LCNEC. Conclusion: We report a case of laparoscopic hepatectomy for liver metastasis of lung LCNEC. It is suggested that surgical resection for solitary distant metastasis of LCNEC may improve prognosis.